ANALISIS KESIAPSIAGAAN PERAWAT INSTALASI RAWAT INAP KELAS 3 TERHADAP BENCANA KEBAKARAN DI RUMAH SAKIT X KOTA SEMARANG - Astari Sari Nastiti; Hanifa Maher Denny; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Preparedness of fire hazard has an important part to be a first step in minimizing losses due to fire. One of those places which have a risk to be burned is hospital. Hospital X have many potential hazards at third class of inpatient installation such as utilization of electricity and utilization of pressured gas cylinder. The purpose of this research was to evaluate nurses preparedness at third class of inpatient installation, room N1, about fire hazard in hospital x Kota Semarang. This was a qualitative research with in depth interview. The subject of this research consisted of six peoples as the main informants and three peoples as the triangulation informants with purposive sampling as the sample technique. The result showed that nurses at third class of inpatient installation have a good knowledge and attitude about fire hazard, Hospital X have a policy and standard operational procedure relate to fire prevention, HSE section make a fire response plan and fire extinguisher, hydrant, sprinkler, detector, alarm is available in this hospital. Nurses have been trained on fire prevention once in every 6-12 months. Hospital X should do a re-socialization about policy and SOP of fire prevention, and organize the simulation once in a year.